MOTIVASI BELAJAR SISWA PANTI ASUHAN AISYIYAH SIDOARJO : STUDI KASUS PADA PANTI ASUHAN AISYIYAH SIDOARJO - miya, Ukti Ullu; Ansyah, Eko Hardi (Program Studi Bimbingan dan Konseling FKIP UMSU, 2023)
This study aims to determine the types of student motivation at the Aisyiyah Sidoarjo Orphanage, the factors that influence student learning motivation at the Aisyiyah Sidoarjo Orphanage, and the efforts made to increase student motivation. This research was conducted with a qualitative descriptive approach. The subjects in this study were 2 teachers, 3 students, and 1 caregiver at the Aisyiyah Sidoarjo Orphanage. The research results show that there is intrinsic and extrinsic motivation, the factors that influence student learning motivation are interest and lack of support facilities. Efforts are given to increase student motivation is to provide objective value, fulfillment of infrastructure facilities, and intensive assistance to students.